The Evolution of Deep Trade Agreements - Mattoo, Aaditya; Rocha, Nadia; Ruta, Michele (World Bank, Washington, DC, 2020)
This paper presents new data on the content of preferential trade agreements. The data contain detailed information on the 18 policy areas most frequently covered in preferential trade agreements, focusing on the stated objectives, substantive commitments, and other aspects such as transparency, procedures, and enforcement. Several new stylized facts emerge: (i) preferential trade agreements have reduced trade-weighted average tariff rates to less than 5 percent for more than two-thirds of countries; (ii) the number of commitments in preferential trade agreements has increased over time, particularly since the 2000s and in areas aiming at facilitating flows of services, goods, and capital; (iii) deepening commitments have been accompanied by an increase in regulatory requirements, namely on enforcement; (iv) developing countries tend to have fewer commitments in preferential trade agreements, with larger gaps in areas such as labor and the environment; and (v) preferential trade agreements are more similar within blocs, but similarity can be significant even across blocs. The paper also discusses the challenges of quantification of preferential trade agreements "depth" and its effects and proposes a research agenda for future work on trade agreements.